TECHNOLOGY OF PEDAGOGICAL SUPPORT OF ARTISTIC AND AESTHETIC DEVELOPMENT OF CHILDREN OF EARLY AGE IN THE CONDITIONS OF INSTITUTIONS OF PRESCHOOL EDUCATION - Ragozina, Victoria (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article deals with the technology of pedagogical support of artistic and aesthetic development of a child of early age in the educational process in institutions of preschool education as a system of interconnected components that contribute to the gradual development of the process of artistic and aesthetic development of the child of early age in art. There is a direct dependence of physical, mental and personal development of children of early age on adults and their participation in children’s lives, Therefore, the author emphasizes the need for a teaching approach as pedagogical support when the child is an equal partner of the educator, who creates conditions for children’s development in their significant activities based on partnership and cooperation. The pedagogical conditions implemented by the technology implemented in the educational process of institutions of preschool education of Sumy city and Sumy region (2020-2021) are determined based on specially developed content, forms and methods of educators’ work with children of early age aimed at the development of their artistic perception, identification of aesthetic emotions in the varieties of artistic and aesthetic art. The content of educators’ work during the three stages of the formative experiment is presented. At the preparatory-organizational stage, training of educators to work in groups of children of early age was initiated. To achieve that goal, educators were introduced to modern scientific approaches to the development of children of early age as well as the course of art and technology of artistic and aesthetic development of children, in particular, perception and discussion of works of art, etc. The attention is paid to the reorganization of the developmental environment in groups of early age according to current principles (labelling of the environment for children, sound and visual signals, etc.), the introduction of up-to-date educational and methodological support. At the technological stage, monthly maps of support of art activities of children of early age with the dominants of formative work for each month, formats of children’s activities during the day were developed in order to ensure the systematic and consistent pedagogical influence. At the productive stage, positive changes were evident in all participants of the educational process (children, educators and parents).